Hodgkin's Disease in Patients with HIV Infection - Michele Spina; Antonino Carbone; Annunziata Gloghini; Diego Serraino; Massimiliano Berretta; Umberto Tirelli (Advances in Hematology)
Hodgkin lymphoma (HL) represents one of the most common non-AIDS-defining cancers with an increasing incidence overtime. Clinically, patients present advanced stages of disease with extranodal involvement in the majority of cases. In the last years, significant improvements in the treatment of patients with HL and HIV infection have been achieved. In the lack of randomized trials, several phase II studies have showed that in the era of highly active antiretroviral therapy (HAART) the same regimens employed in HIV-negative patients with HL can be used in HIV setting with similar results. Moreover, in the last years the feasibility of high dose chemotherapy and peripheral stem cell rescue has allowed to save those patients who failed the upfront treatment. Finally, in the near future, a better integration of diagnostic tools (including PET scan), chemotherapy (including new drugs), radiotherapy, HAART, and supportive care will significantly improve the outcome of these patients.